A method for maintaining vascular access when Impella exchange is required. Issue 6 (22nd May 2017) - Cook, B. Scott; Wilson, Cleve; Kaiser, Brooke; Baljepally, Raj
Abstract : A 45‐year old male with no prior cardiac history, presented with cardiogenic shock in the setting of an anterolateral ST elevation myocardial infarction. We first placed a 2.5 Impella for hemodynamic support, and proceeded with emergent percutaneous coronary intervention to the proximal LAD. Several hours following percutaneous coronary intervention (PCI), the patient became acutely hypotensive and an echocardiogram revealed the Impella catheter was kinked within the left ventricle. The patient was taken back to the cath lab for Impella adjustment; however, damage to the distal catheter required the Impella be exchanged. As the patient was therapeutically anticoagulated and on dual antiplatelet therapy, we modified the Impella catheter in order to maintain existing vascular access during Impella exchange. This case demonstrates our method for maintaining vascular access during Impella exchange, thereby eliminating the need for a second arterial puncture. © 2017 Wiley Periodicals, Inc.